THE “UKRAINIAN CORDOCENTRISM” AS THE METAPHILOSOPHICAL PROJECT - Гнатюк, Я. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article metafilosofskyy design philosophy Ukrainian cordocentrism. Analyzed psychological, textual and metaphilosophical ways of interpretation. Main attention focuses on the conflict between the mythical and interpretations Ukrainian metaphilosophical cordocentrism as the national philosophy.